2017
DOI: 10.17802/2306-1278-2017-2-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Surgical Treatment of Multifocal Atherosclerosis in Different Age Groups

Abstract: Цель. Проведение анализа выживаемости после хирургических вмешательств и изучение факторов, ас-социированных со временем наступления летального исхода у больных с мультифокальным атеросклерозом (МФА) в различных возрастных группах.Материал и методы. Включено 764 последовательных больных в возрасте от 39 до 84 лет с МФА, которым выполнялось изолированное коронарное шунтирование (КШ), либо КШ в сочетании с одномоментными или этапными хирургическими вмешательствами на некоронарных сосудистых бассейнах. Выбор такт… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…For example, Son YJ et al [ 47 ] showed that patients with type D personality are 5 times more likely to have low compliance to prescription drugs than patients without type D 3 months after PCI. In addition, multifocal atherosclerosis in patients with type D personality is detected more often, which is also associated with an unfavorable prognosis in patients undergoing CABG [ 48 , 49 ], as confirmed in our study. We also found a trend toward more frequent detection of cardiovascular risk factors such as smoking and diabetes mellitus in type D. Despite the fact that differences with patients without type D did not reach statistical significance ( p = 0.051 and p = 0.056, respectively), these risk factors also further contributed to a negative impact on the prognosis of personality type D, as and more frequent detection of myocardial infarction and stroke in the history.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Son YJ et al [ 47 ] showed that patients with type D personality are 5 times more likely to have low compliance to prescription drugs than patients without type D 3 months after PCI. In addition, multifocal atherosclerosis in patients with type D personality is detected more often, which is also associated with an unfavorable prognosis in patients undergoing CABG [ 48 , 49 ], as confirmed in our study. We also found a trend toward more frequent detection of cardiovascular risk factors such as smoking and diabetes mellitus in type D. Despite the fact that differences with patients without type D did not reach statistical significance ( p = 0.051 and p = 0.056, respectively), these risk factors also further contributed to a negative impact on the prognosis of personality type D, as and more frequent detection of myocardial infarction and stroke in the history.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, of importance is the state of the vascular system as a whole, which can also affect the course of the disease after coronary artery bypass grafting (CABG). It has now been shown that multifocal atherosclerosis (that is, damage to several arterial basins) adversely affects the prognosis after coronary bypass surgery [ 3 , 4 , 5 ]. These studies included patients with clinical evidence of extra-cardiac vascular disease (history of transient ischemia/stroke, intermittent claudication, decreased ABI < 0.9, need for arterial revascularization) [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies included patients with clinical evidence of extra-cardiac vascular disease (history of transient ischemia/stroke, intermittent claudication, decreased ABI < 0.9, need for arterial revascularization) [ 3 , 5 ]. Although some studies have taken into account subclinical manifestations of extra-cardiac vascular disease (for example, arterial stenosis of more than 50% that does not require surgical treatment [ 4 ]), the impact of such changes on prognosis was not separately assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Risk assessment of cardiac surgery is an essential part of the "Heart team" work and affects the choice of optimal surgical tactics and the decision on the possibility of surgery [1]. Current trends in the standards for provision of high-quality, high-tech medical care are such that patients of older age constitute a large, increasing group due to increasing average patient's age [2,3]. Age is considered one of the factors that significantly affect the outcome of the surgery in the existing scales for assessing the surgery risk (EuroSCORE II, STS, etc.)…”
Section: Introductionmentioning
confidence: 99%